217k views
2 votes
X+8y=-3 solve for y​

2 Answers

5 votes

Answer:

y= (-1/8)X-(3/8)

Explanation:

8y=-X-3

divide over the 8

y=(-1/8)X-(3/8)

User Copser
by
6.5k points
3 votes

Answer:

y = (-x/8) - 0.375

Explanation:

Isolate the variable, y. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS.

First, subtract x from both sides.

x (-x) + 8y = -3 (-x)

8y = -3 - x

Next, divide 8 from both sides.

(8y)/8 = (-3 - x)/8

y = (-3 - x)/8

Simplify.

y = (-x/8) - 0.375

y = (-x/8) - 0.375 is your answer.

~

User Obliquely
by
6.1k points